2012
DOI: 10.1002/btpr.1626
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics and pathway of acid blue 113 degradation byStaphylococcus lentus

Abstract: Bioreaction calorimetric studies of degradation of the dye acid blue 113 by Staphylococcus lentus are reported for the first time. The heat released during the dye degradation process can be successfully measured using reaction calorimeter. Power time and oxygen uptake rate (OUR) profile followed each other suggesting that heat profiles could monitor the progress of the dye degradation in biocalorimetry. The shifts observed in power-time profile indicated three distinct phases of the bioprocess indicating simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Mohammed et al [33] identified 4-diazenyl-1-naphthylamine, 1-naphthyldiazene or 5-diazenyl-1-naphthol as intermediates during the degradation of AB113, which are subsequently mineralized. The intermediate products of the degradation of AB113 are less recalcitrant and are eventually converted to CO 2 and H 2 O [34]. Despite these reported studies, the use of quantum chemical calculation to predict the degradation potential of AB113 by different oxidant has not been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed et al [33] identified 4-diazenyl-1-naphthylamine, 1-naphthyldiazene or 5-diazenyl-1-naphthol as intermediates during the degradation of AB113, which are subsequently mineralized. The intermediate products of the degradation of AB113 are less recalcitrant and are eventually converted to CO 2 and H 2 O [34]. Despite these reported studies, the use of quantum chemical calculation to predict the degradation potential of AB113 by different oxidant has not been presented.…”
Section: Introductionmentioning
confidence: 99%
“…This differences could be attributed to the capability of BioRC1e to handle variables such as agitation (baffles), aeration and precise temperature control. In one of the earlier studies, the differences in mechanism of degradation as a result of shake flask and reactor environment was highlighted (Sekar et al, 2012). The present study emphasises the need for the precise control of bioreactor variables for successful biodegradation process.…”
Section: Carbon Dioxide Evolution Studiesmentioning
confidence: 87%
“…Shigella boydii could remove 100 mg/L of AB-113 with 96% efficiency within 76 h, and when the concentration increased to 500 mg/L, the efficiency decreased to 89% (Senthilvelan et al 2014). Also, Staphylococcus lentus decolorized 25, 50, 75, 100, and 500 mg/L of AB-113 with 92, 79, 62, 60, and 35% efficiencies within 70 h, respectively (Sekar et al 2012). As compared with other studies, microorganisms were not able to remove high concentrations of AB-113 at the same time intervals as the present study, which reveals the high potential of Klebsiella sp.…”
Section: Effect Of Initial Dye Concentrationsmentioning
confidence: 98%